Peripheral Blood Mesenchymal Stem Cells and Platelet Rich Fibrin Matrix in the Management of Class II Gingival Recession: A Case Report - Sphoorthi Anup Belludi; Laveena Singhal; Madhuri Gubbala (Shiraz University of Medical Sciences, 2021)
The treatment of gingival recession is a frequent demand due to aesthetic concern, root caries, and /or root hypersensitivity. The purpose of this case study was to evaluate the success and predictability of coronally advanced flap (CAF) in combination with peripheral blood mesenchymal stem cells (PBMSCs) and platelet rich fibrin matrix(PRFM) for the management of Miller's Class II gingival recession. CAF followed by placement of PBMSCs and PRFM was performed on a male patient, aged 25 years having Miller's Class II gingival recession of 5-6 mm on the upper left canine, premolars and molars. The patient was followed up for 3 months. Root coverage of 60.0% and clinical attachment gain of 3 mm were evident following 3 months of follow-up. This novel technique showed an effective way to increase the width of attached gingiva and treat gingival recession.